Prediction of Self-Concept and Anxiety on the Tendency of Postgraduate Students with Learning Disabilities (LD) to Acquire Research Skills in Two Public Universities of Cross River State, Nigeria: Implications for Counseling - Amalu, Melvina; Uwanda, Ekpang Pauline; Uchechi, Okeke Stella; Ikwen, Emmanuel Uminya; Bekomson, Achi Ndifon; Opoh, Fredrick Awhen; Abang, Kingsley Bekom; Eteng, Matilda Ernest; Nwafor, Patrick Ifeanyi; Ngban, Anthony Ntol; Cklaimz, Enamhe Dorn; Ogbaji, Dominic Ipuole; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
Background: Acquisition of research skills provide the forum for incorporating Nigerian graduate students with disabilities and university lecturers into the international scientific culture and the developing knowledge economy. Aim: This study investigated the prediction of self-concept and anxiety on the tendency of postgraduate students with Learning Disabilities (LD) to acquire research skills in two Public Universities of Cross River State, Nigeria: Implications for counseling. Two objectives of the study were stated to guide the study and to achieve the purpose of the study. Two research questions were formulated, which were converted to two statements of hypotheses. A literature review was carried out based on the variables under study. Method: The survey research design was considered most suitable for the study. A stratified random sampling technique was adopted in selecting the 49 respondents sampled for the study. A validated 20 items four-point modified Likert scale questionnaire was the instrument used for data collection. The face and content validity of the instrument was established by experts in Test and Measurement. The reliability estimates of 0.81 of the instruments were established using the Cronbach Alpha method. A simple Linear regression statistical tool was used to test the hypotheses formulated for the study. The hypotheses were tested at a 0.05 level of significance. Results: The results obtained from the data analysis revealed a significant prediction of self-concept and anxiety on the tendency of postgraduate students with Learning Disabilities (LD) to acquire research skills in the study area. Conclusion: Based on the findings of the study, it was therefore recommended, among others, that internal seminars and workshops should be organized by Graduate schools every quarter of the year, where each postgraduate student delivers a standard paper, and this should be made compulsory. This will encourage sharing knowledge and increase skills and zeal for using knowledge and more research publications.